Evaluation of blast injury patients from the 2015 Tianjin explosions in China. Issue 5 (August 2016) - Yu, Mengyang; Lv, Qi; Ding, Hui; Zeng, Xihuan; Cao, Juan; Liu, Jinyang; Fan, Haojun; Hou, Shike
Highlights: Four types of blast injury were observed in victims after explosion, and most patients sustained multitype trauma. Unexpected prevalence of burns in an open-area explosion. Burns were related to prognosis of patients with blast injuries. Effective triage is important for treatment of survivors after mass casualties involving explosions. Abstract: Objectives: To perform a descriptive analysis of blast injury patients from the Tianjin explosions that occurred August 12, 2015 and provide a reference for triage and treatment of patients in similar situations in the future. Methods: The medical records of patients with blast injuries admitted to our hospital following the 2015 Tianjin explosions were retrospectively reviewed. The results were compared with the literature for other recent mass casualty events. Results: The 75 patients with blast injuries included 58 men (77.3%) and 17 women (22.7%), who had an average age of 36.39 ± 12.3 years. Multidimensional injuries affecting almost every organ system were observed in these patients. The distribution of the types of blast injuries included 36 (48.0%) with primary blast injuries, 63 (84.0%) with secondary injuries, 33 (44.0%) with tertiary injuries and 32 (42.6%) with quaternary injuries. A total of 52 (69.3%) patients suffered more than two types of blast injury. Burns affecting different areas and different depths were present in 41.3% of the patients with blast injuries, and these were divided into the following four groups: a minor group (18.7%), a moderate group (10.7%), a severe group (5.3%), and an extra severe group (6.7%). The total body surface area (TBSA) affected by the burn ranged from 1% to 75%. Additionally, 6.7% of the patients were diagnosed with an inhalational injury, and 2.7% of the patients were diagnosed with chemical poisoning. There were significant differences in the department distribution (especially in the burn unit and ophthalmology department) and ICU treatment between civilians and firefighters. Conclusion: Various types of injury, with overlapping injuries present in many patients, were observed in the victims after the Tianjin explosions. An evaluation of the distribution of blast injuries is important for optimizing strategies to triage and treat survivors after mass casualty events.